2014
DOI: 10.1179/2047773214y.0000000137
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of West Nile Virus infection in the region of Monastir, Tunisia, 2003

Abstract: West Nile virus is a reemerging global pathogen that remains an important public health challenge in the next decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 69 publications
2
20
0
Order By: Relevance
“…The bio-ecological characteristics of the species as well as certain environmental factors have favored the emergence of this virus in a previously free area. Many outbreaks of human WNV infections were identified in Tunisia in 1997, 2003 and 2012 [27][28][29][30]. Last authors reported sporadic cases in 2007, 2010, and 2011.…”
Section: Discussionmentioning
confidence: 99%
“…The bio-ecological characteristics of the species as well as certain environmental factors have favored the emergence of this virus in a previously free area. Many outbreaks of human WNV infections were identified in Tunisia in 1997, 2003 and 2012 [27][28][29][30]. Last authors reported sporadic cases in 2007, 2010, and 2011.…”
Section: Discussionmentioning
confidence: 99%
“…This mosquito is strongly fought, especially by the use of insecticides because of the nuisance that it causes and its transmission of West Nile Virus [1][2][3][4]. For years, the organophosphates (OPs) and synthetic pyrethroids have been widely used in the mosquito control programs.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of the sensitivity of culicidae to insecticides is essential for guidelines of any vector control program to ensure timely control of the situation when the insecticide is no longer effective. Culex pipiens mosquito has been strongly suspected as the most likely vector in the transmission of West Nile virus outbreaks that have affected Tunisia in 1997, 2003, 2007, 2010, 2011and 2012(Triki et al, 2001Hachfi et al, 2010;Bouatef et al, 2012;Riabi et al, 2014). With the exception of the work of Ben Cheikh et al (1995;1998) and Tabbabi et al (2017), no other studies have been published on the susceptibility of culicidae to temephos (organophosphates (OP)).…”
Section: Introductionmentioning
confidence: 99%